The application of computer aided design as a tool for building user-centered design in consumer ceramics’ product development - Olalere, Folasayo Enoch; Ab. Aziz Shuaib; Ramli Ismail (2012)
This paper investigates the knowledge regarding how user-centred design can be built in ceramic consumer products. The paper gives the general overview of ceramics, computer-aided design and its application in ceramic product development. It also illuminates on product emotion, its influence on consumers’ behaviour and how it can be integrated into new product conceptualization. Furthermore, the paper analysed the systematic approach in building user-centred design in new product and also reveals how CAD can be used to achieve a user-centred design. In order to test the viability of CAD in achieving user-centred design, a study was performed where a CAD-model of a multi-functional ceramic pot was created and a questionnaire with the image (CAD model) and eight emotions was given to participants so as to know their emotional responses toward the product. The result from the study reveals the viability of computer aided design as tool for building user-centred design in consumer ceramics’ product development